Yield and Yield Attributes of Short Duration Mustard as Influenced by Nutrient Rates - Ahamed, KK; Karmakar, B; Ahamed, B; Akter, S; Islam, MS (Bangladesh Agronomy Journal, 2020)
Mustard (Brassica napus)is the important principal edible oil-producing crop in Bangladesh. However, the nutrient requirement of mustard especially for the short duration variety is very much important to obtain higher yield. A field experiment was conducted to assess the requirement of major nutrients (N, P, K, and S), and to recommend fertilizers for short-duration mustard variety BARI Sarisha-14. There were 8 treatments T1=100% soil test based (STB) nutrients (N, P, K, S, Zn & B @ 90, 25, 60, 15, 2 & 1 kg ha-1, respectively) as per Fertilizer Recommendation Guide (FRG,2012), T2=T1+ 25% N of FRG, T3=T1+ 25% NP of FRG, T4=T1+ 25% NK of FRG, T5=T1+ 25% PK of FRG, T6=T1+ 25% NPK of FRG, T7=75% of T1 and T8= native nutrient (control). The experiment was laid out in Randomized Complete Block Design with 3 replications. The results revealed that yield and yield parameters of mustard weresignificantly influenced by the nutrient levels. The highest value of almost all the yield components and yield were obtained in T6 among the treatments. The highest seed yield (1.68 t ha-1) and the maximum stover yield (2.96 t ha-1) were obtained from the treatment (T6) containing 100% STB nutrients with additional 25% NPK among the fertilizer treatments. The seed yield value was statistically higher than all other treatments except the treatment where100% STB nutrients with additional 25% NP were used (T3). The highest seed yield and stover production were attributed tothe yield contributing parameters. The highest amount of all the nutrients content was found in the treatment T6 that was followed by T3 and T4 and the lowest in T8. The highest amount of N, P, K, and S content in seed of the treatment T6 was 3.75, 0.97, 0.96 and 0.78%, respectively. The highest yield was accredited to the highest amount of nutrient content in seed. It could be concluded that the treatment T6 (STB fertilizer dose + 25% NPK of FRG) would suitable for short duration Mustard (BARI Sarisha-14) for getting higher yield and better performance. Bangladesh Agron. J. 2019, 22(2): 129-138